CARA BIJAK HUKUM ISLAM MENYEMAI CINTA DAN MEMBINA RUMAH TANGGA - Muh. Sudirman; Dr. Mustaring Mustaring (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2022)
Islamic law has its own tips and rules in sowing love and building a family. The normative rules of Islamic law are different from the rules and culture that apply today, especially the rules and culture which are the influence of modern lifestyles from the West. The culture of promiscuity, anti-marriage, marriage and divorce, and the like are not in line with the norms of Islamic law. Muslims wherever they are must maintain and practice their religious teachings so that they are not easily influenced by the many cultures of the opposite sex that do not pay attention to social responsibility for the future of children. Islamic law has rules regarding the association of men and women before and after marriage. Pre marriage, men and women may not lead to adultery. After marriage, the husband and wife must carry out their obligations, so that all parties can obtain their respective rights proportionally. Besides that, husband and wife must be smart in choosing attitudes, behaviors and words that can please their partner, so that family happiness (love) can last.